Method for manufacturing all-solid-state battery

By alternately coating the slurry of active substances and electrolyte particles, an electrode and electrolyte layer with high adhesion and low interface resistance is formed, which solves the problem of insufficient residual carbon and interface adhesion in the manufacturing of all-solid battery, and improves battery performance and Productivity.

CN113261143BActive Publication Date: 2025-02-07MTEK SMART
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980088106.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-09
Filing Date
2019-12-27
Publication Date
2025-02-07
Estimated Expiration
2039-12-27

AI Technical Summary

Technical Problem

The existing all-solid battery manufacturing method generates residual carbon during the sintering process, and the interface adhesion between the electrode layer and the electrolyte layer is insufficient, which affects the battery performance.

Method used

By using an alternating coating method, a slurry composed of active substances and solvents and a slurry composed of electrolyte particles or fibers and solvents are formed into a thin film, forming an electrode and an electrolyte layer with high adhesion and low interface resistance.

Benefits of technology

The production efficiency of the battery is improved, the residual carbon during sintering is reduced, the interface surface area between the electrode layer and the electrolyte layer is increased, the interface resistance is reduced, and the battery performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113261143B_ABST
    Figure CN113261143B_ABST
Patent Text Reader

Abstract

[Topic] In the process of forming electrodes for all-solid batteries, prevent the aggregation of electrode active materials or electrolytes, layer them in the required ratio of active material mass and electrolyte mass, and mix microscopic particles evenly. At the same time, in order to achieve a uniform thin film electrolyte layer, it is further made into a thin film for layering. Make the gaps between particles disappear or minimize them as much as possible, improve the adhesion of each interface and reduce resistance. Prevent the conductive additive from agglomerating unevenly or forming a film structure. Eliminate or minimize the residual carbon caused by the binder to improve battery performance. [Solution] Make the slurry mainly composed of electrode active materials and solvents, or the slurry mainly composed of electrolyte particles and solvents alternately impact the target object with impact force and make it adhere and layer on the film, thereby forming a high-density layer to improve adhesion. Separately manufacture a slurry mainly composed of a conductive additive and a solvent, and apply it in small amounts at the desired location. Remove or reduce the residual carbon by excluding or minimizing the binder content to improve battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an all-solid-state battery, wherein particles containing active materials and the like are made into a slurry to form electrode layers at both poles, electrolyte particles are made into a slurry to form an electrolyte layer, and the all-solid-state battery is formed by a laminate formed by a positive electrode layer, an electrolyte layer, and a negative electrode layer. In the detailed description, the manufacturing method of the all-solid-state battery is mainly described, but the manufacturing method is applicable to all battery manufacturing processes, that is, it is also applicable to manufacturing processes such as metal air batteries, which are hailed as the next generation of batteries. The present invention relates to a method for manufacturing an all-solid-state battery, specifically, a method for forming an electrode by directly coating a slurry composed of electrode active material particles and a slurry composed of electrolyte particles or fibers on a target object.

[0002] The coating of the present invention is not particularly limited, and includes a method of coating the object by roller coating, slit die (slit nozzle) coating, screen printing, curtain coating, or atomization (including fiberization) including dispersion (dispense), inkjet and injection, and even electrostatic atomization (including fiberization) and other embodiments to form particles or fibers, and also includes a coating method using a micro curtain method.

[0003] The so-called micro-curtain method is a method of spraying liquid at a relatively low pressure of about 0.3MPa using a wide-angle vacuum spray nozzle, etc., and using the liquid film before the mist is formed and moving the object to be coated and the spray nozzle relative to each other to perform coating. This method does not form excessive spray particles on the coating surface. This method uses the physical property that it becomes mist after passing through the object to be coated and leaving a certain distance.

[0004] Atomization (fibrillation) refers to a method of applying a coating by using atomization, in addition to granulation by spraying, to disperse and atomize a liquid containing solid microparticles by using ultrasound, and to granulate and fibrillate by rotating by electrospinning or by using the centrifugal force of a rotating body. The method also includes a method of applying a spray method to a liquid to produce particles or fibers. Since the directionality of the particles atomized by ultrasonic atomization or centrifugal atomization is unstable, the particles are attached or coated on the target object with the help of compressed gas (airassist).

[0005] In the present invention, these methods are collectively referred to as spraying methods for explanation. Background Art

[0006] As the number of mobile electronic devices (mobile phones) and electric vehicles increases, there is a growing demand for fast charging of rechargeable batteries including lithium batteries, but electric vehicles take tens of minutes to fully charge. Due to issues such as the length of time and safety risks, a method is currently being developed to change the electrolyte from liquid to solid and shorten the charging time required to complete 80% of the total charge to a few minutes.

[0007] Patent document 1 proposes a method for manufacturing a layer structure of a solid electrolyte layer, a positive electrode active material layer, and a negative electrode active material layer of an all-solid-state battery, wherein a slurry containing materials constituting the layer structure is modulated to form a green sheet, and the green sheet is integrally formed with a sheet having concave and convex portions that disappear upon heating. This method forms concave and convex portions on the surface of the green sheet, and finally the integrally formed green sheet and the sheet are heated together, and finally the sheet disappears and the cold green sheet is sintered, thereby forming an electrode while forming a concave and convex structure on a substrate.

[0008] Patent document 2 proposes a polyvinyl acetal resin that can be degreased at low temperature and in a short time, which can be used to form and laminate electrode layers and electrolyte layers of all-solid batteries, electrode slurries composed of active material particles, solvents, and binders, and electrolyte slurries composed of electrolyte particles, solvents, and binders. Specifically, it is to apply solid electrolyte slurry, negative electrode, or positive electrode slurry on the support layer of the PET film after demolding, and peel off the PET film after drying at 80°C for 30 minutes, and then sandwich the electrolyte layer with the negative electrode and positive electrode active material layers and heat and pressurize at 80°C and 10KN to obtain a laminate, and apply a conductive binder containing acrylic resin on a stainless steel plate to make a collector, and finally sinter at a temperature of 400°C in a nitrogen environment to degrease the binder.

[0009] Although in the method of patent document 1, the contact area between the active material layer and the electrolyte layer can be ideally increased by coating the active material slurry and the electrolyte slurry on a polyvinyl alcohol sheet having a concave-convex structure, there is a problem: this method requires the use of high temperature and a long time (for example, 50 hours at a high temperature of 700°C) to completely remove the resin.

[0010] In the method of patent document 2, in order to achieve the purpose of volatilizing the solvent components of the slurry, a volatilization process is required at a temperature of 80°C for 30 minutes, which will cause a new problem in the production line of lithium-ion batteries: under the current production line speed (for example, 100 m / min), the production line length has to be lengthened, or the production line speed has to be reduced without changing the production line length.

[0011] Regardless of the above methods, if the binder in the slurry is removed or reduced, the slurry tends to precipitate particles at the stagnant location in a general circulation device. In addition, the die used in the process of forming the electrode of the lithium battery cannot be used for coating construction.

[0012] Prior art documents

[0013] Patent Documents

[0014] Patent Document 1: International Publication No. 2012 / 053359

[0015] Patent document 2: Japanese Patent Application No. 2014-212022 Summary of the invention

[0016] (Problems to be solved by the invention)

[0017] The present invention improves production efficiency and eliminates or minimizes the residual carbon generated during sintering of the laminated body that needs to be sintered. The present invention also improves the tightness of the interfaces of each laminate. At the same time, the present invention increases the interface surface area of ​​the electrode layer and the electrolyte layer, reduces the interface resistance and improves the battery performance. However, in the electrode layer, the coating is formed by mixing the electrode active material with the electrolyte particles or fibers to form a slurry. Although this method has excellent mixing and dispersion effects, it is necessary to solve the problem of agglomeration over time that causes performance degradation.

[0018] The present invention is applicable to the case where the type of solid electrolyte particles is sulfide or oxide, and is also applicable to the case where the active material particles for the positive electrode or the negative electrode are of various types.

[0019] For example, when the electrolyte is a sulfide (such as LPS), the positive electrode can be lithium sulfide (Li2S) particles or sulfur (S8), and the negative electrode can be graphite and silicone particles.

[0020] (Technical solutions to solve problems)

[0021] The present invention is completed to solve the above-mentioned problems. The purpose of the present invention is: when manufacturing high-quality all-solid batteries, the slurry mainly composed of active materials for positive electrodes, and the slurry composed of electrolyte particles or short fibers and solvents can be independently layered on the collector in a thin film manner using a coating device. Similarly, the slurry mainly composed of active materials and solvents for negative electrodes, and the slurry mainly composed of electrolytes and solvents are alternately coated on the collector of the negative electrode in a thin film manner. At the same time, solutions, emulsions, inorganic or organic particles or fibers (such as PTFE or PVDF, etc.) powders, electrolyte glass fibers, etc. as binders are mixed in each slurry. The particle or fiber binder is dispersed in a slurry with a solvent, or it can be independently layered and coated alternately as needed, independent of the slurry composed of active materials and electrolyte particles. The coating device is not limited to the above-mentioned device. If a slurry consisting of particles and a solvent, or a slurry consisting of particles, a solvent, and a binder between particles can be granulated by a spray or particle generating device, and the particle speed is adjusted to a desired speed so that it impacts the target object with impact force, the effect of the particles being tightly and firmly attached to the target object after the solvent evaporates is significant.

[0022] The target object refers to the positive electrode layer, negative electrode layer, electrolyte layer, and current collector. When electrode slurry particles are attached, the target object is the current collector or electrolyte layer, and when electrolyte slurry particles are attached, it is mainly the positive electrode or negative electrode layer. It also includes the case where electrolyte particles are attached to the current collector together with particles of positive electrode and negative electrode active materials to form an electrode.

[0023] The present invention provides a method for manufacturing an all-solid-state battery, which forms electrode layers on positive and negative electrode collectors of the all-solid-state battery, forms an electrolyte layer on at least one of the electrode layers, and inserts a closely-contacted positive electrode layer, electrolyte layer, and negative electrode layer between the positive electrode collector and the negative electrode collector, or inserts an electrolyte layer into the electrode layers for stacking. The manufacturing method includes: when forming the electrode layer on the collector, preparing at least a slurry consisting of an electrode active material and a solvent, and a slurry consisting of electrolyte particles or electrolyte short fibers and a solvent; and a stacking step of alternately coating at least the two types of slurries on the collector in a thin film manner to form more than two layers respectively.

[0024] The present invention provides a method for manufacturing an all-solid-state battery, wherein each slurry has 2 to 15 layers.

[0025] The present invention provides a method for producing an all-solid-state battery, wherein at least a positive electrode slurry of the slurry contains a conductive auxiliary agent.

[0026] The present invention provides a method for manufacturing an all-solid-state battery, wherein the conductive aid is prepared as a separate slurry, and the conductive aid particles or fibers are dispersed in a manner such that at least the conductive aid particles or fibers do not form a film, and are coated on electrolyte particles, fibers, or active material particles.

[0027] The present invention provides a method for manufacturing a fully solid battery, wherein at least the electrode slurry and the electrolyte slurry contain an inorganic or organic binder.

[0028] The present invention provides a method for manufacturing an all-solid-state battery, wherein an electrolyte layer is formed by laminating an electrolyte layer slurry in a thin film manner on a positive electrode layer or a negative electrode layer forming the electrode, or on a porous sheet for an electrolyte.

[0029] The present invention provides a method for manufacturing an all-solid-state battery, wherein at least one of the electrode formations described in the present invention is applied by spraying or by granulating the slurry and moving it, and the collector, electrode layer, and porous sheet serving as the coating target are heated, and within 5 seconds after the sprayed particles or the granulated slurry are attached to the target, more than 95% of the solvent is evaporated to form an electrode or electrolyte layer.

[0030] The present invention provides a method for manufacturing an all-solid-state battery, wherein the spraying is performed in a pulse mode of 1 to 1000 Hz, the distance between the target object and the nozzle is 5 to 60 mm, the slurry spray particles are sprayed with impact force toward the target object, the solvent and non-volatile components of the slurry are instantly separated and the solvent evaporates.

[0031] The present invention provides a method for manufacturing an all-solid-state battery, wherein the electrolyte is a sulfide, an exhaust means is connected downstream of the assembly line of the electrode layer formation and electrolyte layer formation steps, and a dehumidification means is provided upstream.

[0032] The present invention provides a method for manufacturing an all-solid-state battery, comprising: a process of forming a negative electrode on a negative electrode collector, a process of forming a positive electrode on a positive electrode collector, a process of forming an electrolyte layer on the negative electrode or on the positive electrode, or a process of forming an electrolyte layer with a porous substrate as a skeleton and interposing an electrolyte layer between the positive and negative electrode layers for stacking.

[0033] The present invention provides a method for manufacturing an all-solid-state battery, wherein the all-solid-state battery is manufactured by a roll-to-roll method.

[0034] In the present invention, the electrolyte is not limited to sulfide or oxide, and the amount of binder used in each slurry, especially when sintering is performed in the subsequent process, is preferably less than 10% of the total weight of the solid component in terms of weight ratio, and preferably less than 2% from the viewpoint of leaving as little residual carbon as possible. When a binder is present, a potential difference is provided between the target object, the slurry, or the microparticles formed after granulation by spraying, etc., so that the adhesion of the microparticles can be promoted by electrostatic action. Such electrostatic coating is particularly effective for adhering submicron or smaller ultrafine particles. In order to make the sprayed particles etc. electrostatically charged, the above-mentioned binder or solvent should be selected to be easily charged by static electricity.

[0035] According to the manufacturing method of the all-solid battery of the present invention, the sprayed particles can be impacted on the target object with impact force and attached to form an ultra-tight particle group. In addition, it is easy to form fine bumps on the electrode interface or bumps of the required size as needed, so that the contact area with the electrolyte layer can be increased to enhance the adhesion by using the anchoring effect and minimize the interface resistance.

[0036] In the present invention, the positive electrode layer, the electrolyte layer, and the negative electrode layer can be formed into a laminate by granulating the electrode slurry or the electrolyte slurry by spraying or the like and then laminating. The positive electrode layer and the negative electrode layer can be made into a slurry by mixing the electrode active material particles with the electrolyte particles or the electrolyte short fibers with a solvent, and adding a conductive auxiliary agent to the binder (especially in the positive electrode) as required, and then laminating the electrode layer on the film by die coating, roller coating, curtain coating, screen coating, etc. to increase the processing speed. At the same time, the electrolyte layer can also be formed in the same way, or the required slurry, solvent, or binder solution with less solid content can be granulated and attached with impact force at the interface of the positive electrode layer, the electrolyte layer, the negative electrode layer, and only at the interface of the collector to finally form a laminate.

[0037] In addition, in the present invention, with respect to the electrode, it is not limited to a single slurry formed by mixing various types of particles, and various slurries of different types can also be prepared and multiple nozzles can be used correspondingly. No matter how evenly the slurry containing no or only a small amount of binder is mixed by mixing particles of different specific gravities or particle sizes (such as particles for electrodes and particles for electrolytes), it will change its dispersion state over time or settle instantly. If a slurry mainly composed of active material particles for electrodes and a solvent and a slurry mainly composed of electrolyte particles or fibers and a solvent are prepared separately, and the spraying amount is modulated according to their respective required ratios, and they are overlapped in a desired manner in a thin film manner (for example, alternately stacked in several layers), an ideal electrode laminate can be obtained. This method is also effective for the desired distribution and stacking of conductive aids such as active materials, carbon particles, carbon nanofibers, etc. with significantly different unit volume ratios, specific gravities and particle sizes. Too little or too much conductive aid in the unit volume of the electrode layer will affect the performance, so compared with the application method of mixed slurry mixed with active materials, the present invention can greatly improve the performance. In addition, the present invention can mix inorganic or organic particles, fiber binders (such as resin powders or short fibers such as PTFE or PVDF), electrolyte glass short fiber binders, etc. with solvents or add resin solutions or emulsions as needed to form slurry, and apply the required amount of the slurry separately to the required position.

[0038] Conductive additives reduce the solid content concentration in the slurry. For example, if the slurry is made into a thin film and layered in a manner entangled with electrolyte particles or active material particles in a slurry state with a solid content concentration of less than 10%, the coating amount per unit area becomes more uniform, which can improve the performance of the battery.

[0039] In addition, in the present invention, in order to prevent the performance degradation caused by the expansion and contraction of the silicone and silicon oxide particles effective for the negative electrode, a strong adhesive can be applied to a part of the silicone particles. That is, different nozzles are used to combine the slurry composed of silicone particles with a strong adhesive solution or emulsion, resin particles, or fibers to form particles and layer them, and the adhesive particles are attached to a part of the silicone surface to form an electrode layer. In order to make the adhesive into a spray or fine particles and make it move and attach to a part of the silicone surface, it is most appropriate to use a pulse method with impact force. It is also possible to add carbon particles of the negative electrode active material to the adhesive solution or adhesive emulsion to form a slurry and then apply it.

[0040] The target object can be heated. The heating temperature is preferably 30 to 150°C. By heating the target object, the solvent component of the granulated slurry can come into contact with the target object, become wet, and evaporate at the same time. The time required for 95% of the solvent to evaporate is preferably within 5 seconds, and more preferably within 2 seconds. As time increases, the particle group with impact force and high density accumulation tends to loosen in the solvent. If all the solvent is evaporated instantly at the same time as the impact, the solvent vapor will make the spray particles and the like easily fly away, and it is easy to cause sudden boiling in the binder.

[0041] In the present invention, when the slurry is granulated and attached to the target, the impact force can be enhanced by a pulse method. In particular, in the air jet method known as dual-fluid jet in the industry, the mass of air around the jet particles is as much as 400 to 600 times, which causes the particles that arrive at the target relatively late to be bounced back into the air by the target, resulting in not only the loss of impact force, but also the extremely poor adhesion efficiency of the particles. On the other hand, in the impact pulse method in which both the slurry and the air are pulsed, the air compressed between the jet particle group and the jet particle group will diffuse, and only particles with directionality will move and attach. As a result, the adhesion efficiency can be increased from only 30 to 50% of the usual jet to more than 95%, so the method of the present invention has an economical effect. In addition, the pulse method can control the coating amount of conductive additives, such as conductive additives, to less than one-tenth of the usual jet, which is very convenient when adjusting the ratio of conductive additives to electrolytes or active materials of electrodes.

[0042] (Effects of the Invention)

[0043] As described above, according to the present invention, a high-performance all-solid-state battery can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 FIG. 1 is a schematic diagram showing a method of spraying an active material onto a target object (current collector) according to an embodiment of the present invention.

[0045] Figure 2 Schematic diagram showing the spraying of electrolyte particles or various types of particles (such as a conductive auxiliary agent) onto active material particles adsorbed on a target object according to an embodiment of the present invention.

[0046] Figure 3 FIG. 1 is a cross-sectional view showing a stack of two types of particles according to an embodiment of the present invention.

[0047] Figure 4 It shows a cross-sectional view of a current collector, a positive electrode layer, an electrolyte layer, a negative electrode layer, and a current collector according to an embodiment of the present invention stacked.

[0048] Figure 5FIG. 1 is a cross-sectional view showing the state in which the electrode slurry is sprayed onto a target object (current collector, electrolyte layer) according to an embodiment of the present invention.

[0049] Figure 6 It is a cross-sectional view showing the spraying of the target object (electrolyte layer, electrode layer) according to the embodiment of the present invention.

[0050] Figure 7 It is a cross-sectional view showing the spraying of a target object (electrolyte layer) according to the embodiment of the present invention.

[0051] Figure 8 It shows a cross-sectional view of a target object (current collector) according to an embodiment of the present invention being sprayed alternately in a pulsed manner with a time difference to deposit various materials. DETAILED DESCRIPTION

[0052] Next, the preferred embodiment of the present invention is described with reference to the accompanying drawings. It should be noted that the following embodiment is only an example for easy understanding of the invention, and those skilled in the art may add, replace and deform the same without departing from the scope of the technical concept of the present invention, which are all included in the scope of the present invention.

[0053] The drawings illustrate preferred embodiments of the invention.

[0054] like Figure 1 As shown in , a slurry consisting of active material particles for electrodes and a solvent, or a slurry consisting of an active material, a solvent, and a binder is sprayed from a nozzle 21, so that the active material spray particles 2 are attached to the target collector 1. The type of active material particles is arbitrary, but when the electrolyte is a sulfide, the active material used as the positive electrode, such as lithium cobalt oxide (LCO), lithium nickel manganese cobalt oxide (NMC), nickel cobalt aluminum lithium oxide (NCA), etc., reacts with sulfur and hardly allows lithium ions to pass through, so these active materials can be covered with a thin film of lithium niobate or the like to form particles. The active material particles or electrolyte particles are respectively encapsulated with the electrolyte or the active material, which can shorten and simplify the process, so it is efficient in terms of production. The spraying is performed in a pulsed manner, and the particles are attached to the collector with impact force when the spraying speed is fast, so that the tight adhesion can be improved. In order to make the sprayed particles 2 have impact force, the distance between the target object and the nozzle can be as close as possible, for example, it can be controlled to be 5 to 60 mm, and a two-fluid nozzle with a narrow spray angle (for example, less than 30 degrees, preferably less than 20 degrees) is used to spray in a pulsed manner at a gas pressure of 0.15 to 0.3 MPa. Considering productivity, the number of pulses per second is preferably 10 Hz or more.

[0055] The shorter the distance and the narrower the spray angle, the better the impact force.

[0056] In addition, a slurry mainly composed of electrolyte particles and a solvent may be sprayed at the beginning.

[0057] The room for coating and spraying is preferably a spray booth with good exhaust gas. When the electrolyte is a sulfide, the supply gas needs to be dehumidified. Regarding dehumidification, low dew point dehumidification is better. For example, when the temperature is set to minus 100°C, almost no hydrogen sulfide is produced. Thus, a solid-state battery with good performance can be obtained. In addition, for materials that are easily oxidized, it can be carried out in an inert gas atmosphere (such as argon, etc.) according to the needs of the heating process, etc., so as to suppress the reaction.

[0058] Figure 2 It means that Figure 1 The figure shows a state where various slurries such as electrolyte particles are sprayed around or on the top of a layer of active material 2' attached to the thin film in FIG. 2 and the particles 3, 3' are dispersed and coated on the thin film. Figure 1 The spraying of active material from nozzle 21 and the spraying of electrolyte from nozzle 22 can alternately stack any layers in a thin film manner. And the electrolyte particles can be replaced or added to the electrolyte particles with at least one conductive aid selected from carbon particles, carbon nanofibers, and carbon nanotubes, a solution or slurry composed of conductive aids such as lithium iodide, and a slurry mixed with electrode active materials or electrolyte particles can be further added thereto, and it can be sprayed from nozzle 22 to attach the spray particles 3. The larger the surface area of ​​carbon or nanocarbon with pores in the conductive aid, the better, preferably more than 2000 square meters per gram in the BET chart, more preferably more than 3500 square meters. If this condition is met, sulfur or active materials can be encapsulated in the nano-scale pores of the positive electrode, and nano-scale silicon can be encapsulated in the nano-scale pores of the negative electrode to improve the electrode performance.

[0059] Figure 3 The figure shows an alternately stacked electrode active material 2' and electrolyte particles 3', and the weight ratio per unit area can be freely selected, and the ratio can be easily adjusted by selecting the pulse frequency when performing pulse spraying. In addition, a predetermined amount of conductive additive can be dispersed and applied around the electrolyte or electrode active material in a predetermined amount by using other nozzles to make it adhere.

[0060] Figure 4 The figure shows that the positive electrode layer 11 and the negative electrode layer 13 are stacked on both sides of the electrolyte layer 12, and then the electrodes 11 and 13 are sandwiched between the collectors 1 and 10 and pressed under heating or room temperature to form a stacked body for an all-solid-state battery. Generally, the collector can use aluminum foil for the positive electrode and copper foil for the negative electrode, but stainless steel thin plates can also be used depending on the type of active material or electrolyte, and the present invention is not particularly limited.

[0061] Figure 5 The figure shows that in order to form a negative electrode layer on the positive electrode collector 1, the positive electrode layer 11, the electrolyte layer 12 and the negative electrode collector, the electrolyte slurry is sprayed alternately from the nozzle 24 and the negative electrode active material slurry is sprayed from the nozzle 23, and the rollers 31 and 31' are pressed. In the subsequent process, when the pressing is performed, the pressing pressure can be almost zero or a low pressure can be used. The rollers can be heated, and the collector, the electrode layer, and the electrolyte layer can be heated in advance to promote the volatilization of the solvent contained in the sprayed particles 4 and 5.

[0062] Figure 6 It is shown that the electrolyte slurry or the electrode active material slurry, or both, is sprayed at the interface between the electrolyte layer 12 and the negative electrode layer 13 by the nozzle 25. It is also possible to spray a slurry composed of electrolyte particles and electrode active materials. The close adhesion of the interface can be improved by spraying a solvent, etc., so that the respective interface adhesives, etc. are instantly moistened. The rollers 31, 31' can be moved without pressure or pressing. The present invention does not particularly limit the load, diameter and number of the pressing rollers.

[0063] Figure 7 The figure shows a diagram of spraying electrolyte layer slurry or solvent on the electrolyte layer formed on both the flexible collector, the positive electrode layer, and the negative electrode layer. The effect is the same as the above. A separately manufactured electrolyte sheet or a flexible electrolyte membrane filled in a porous substrate can be sandwiched between the positive and negative electrodes without an electrolyte layer. In this case, the electrolyte slurry, the corresponding active material slurry, the binder solution or the solvent can also be applied to the surface of the electrolyte or the surface of each electrode to improve the adhesion.

[0064] Figure 8The figure shows the situation where the negative electrode active material slurry is sprayed on the negative electrode collector 10 in a pulsed manner from the nozzle 23 to form the spray particle group 7. One of the electrolyte slurries is sprayed out from the nozzle 24 in a pulsed manner to form the spray particle group 8, whereby various different spray particle groups are alternately layered on the negative electrode collector. Multiple layers can be layered on the film. Similarly, a slurry mainly composed of a positive electrode active material and a solvent, and a slurry mainly composed of an electrolyte and a solvent can also be alternately layered on the positive electrode collector. Although not shown in the figure, a nozzle can also be added to alternately spray the conductive auxiliary agent slurry with the nozzle 23 or the nozzle 24 in a pulsed and trace manner. When the electrolyte is a sulfide, in order not to generate hydrogen sulfide in this operation procedure, it should be carried out in an environment that has been sufficiently dehumidified. In addition, the target object can be a collector or a porous sheet equivalent to the roller gap size, or a single collector or a porous sheet, or a sheet with an electrode formed on the collector. The electrode can be intermittently coated at the end of the collector with a slit nozzle to form the periphery (edge) of the tab for laser welding. In addition, a mask can be used to apply at the closest distance during the spraying process to form the periphery (edge).

[0065] In the present invention, in order to improve production efficiency, a slit nozzle or the like can be used to coat a target object with a width of 1500 mm at high speed. In addition, 100 to 200 nozzles for each coating of one type of slurry layer can be arranged in one or more rows in a direction perpendicular to the moving direction of the target object to form a nozzle group for spraying or spraying with pulse impact force. As needed, the nozzle group can also be reciprocated (shaken) 15 mm in the nozzle arrangement direction to fully cover the range of the 15 mm pattern. At the same time, the nozzles configured according to the required type of slurry or the nozzles configured according to the required number of layers can also be arranged to correspond to different speed requirements.

[0066] When it is necessary to simplify the structure of the nozzle, it can be done on the wide roller disclosed in Japanese Patent Laid-Open No. 8-309269 invented by the inventor. The invention discloses that grooves are formed at a certain distance (such as 10 mm) in the width direction of the wide roller, the roller is rotated, and the slurry filled in the groove is granulated with compressed gas to adhere to the target. Theoretically, the speed of the target can be set to more than 100 meters per minute. At the same time, the roller device can also be configured perpendicular to the moving direction of the target according to the slurry for a few minutes or the number of layers for a few minutes. At the same time, the technical content disclosed in Japanese Patent Laid-Open No. 6-86956 invented by the inventor can also be used. A large number of card controls can be set through a cylindrical screen or seamless belt that is wider than the width of the target. The diameter of the opening can be 150 microns, and the slurry is filled in the hole of this scale, and then liquefied gas or compressed gas is blown out at a position opposite to the target to granulate it into tiny particles so that it can be evenly attached to the entire surface of the target. If the screen printing roller screen sold on the market is used, the cost is low. In addition, the same technical effect can be obtained by forming holes with a diameter of 0.3 mm or 0.5 mm in a staggered manner with a spacing of 1.5 mm on a cylindrical tube wider than the width of the target object.

[0067] In the above two methods, the distance between the blowing position after granulation and the target object is set to 5 to 70 mm, because the impact effect is improved, which is preferred.

[0068] In the above two methods, production line tracking is achieved by using a volumetric supply method and changing the rotation speed. This method does not require expensive pumps and controllers, and can be designed and modified on the roll-to-roll extension line of a roller coater or a rotary screen coater, so that production can be carried out by modifying some existing lithium battery electrode production lines.

[0069] In the present invention, a method of making slurry into particles and moving them by pressure difference can be used. The granulation can be inkjet, or a rotary atomization device such as a disc or bell used in the general coating field can be used to micronize it. In addition, a method such as a bubbler or ultrasonic wave to form atomization, a jet flow and a close impact on a rotating roller to achieve micronization can be used. The granulated particle group can be moved by a carrier gas and attached to the target by pressure difference.

[0070] If the movement is performed in a pulsed manner, the adhesion efficiency and the impact force will increase, which is therefore preferred.

[0071] (Industrial Applicability)

[0072] According to the present invention, a laminate composed of an electrolyte, an electrode, and a current collector for an all-solid-state battery having low interface resistance and high adhesion can be produced with high quality.

[0073] (Explanation of symbols)

[0074] 1: positive electrode collector; 2, 4: electrode active material spray particles; 2': electrode active material; 3, 5: electrolyte spray particles; 3': electrolyte particles; 6: solvent and other spray particles; 7: electrode active material spray particle group; 8: electrolyte spray particle group; 10: negative electrode collector; 11: positive electrode layer; 12: electrolyte layer; 13: negative electrode layer; 21, 22, 23, 24, 25: nozzles; 31, 31': rollers.

Claims

1. A method for manufacturing an all-solid-state battery, characterized in that: Electrode layers are formed on current collectors for the positive and negative electrodes of the all-solid-state battery, and an electrolyte layer is formed on at least one of the electrode layers. A closely-contacted positive electrode layer, electrolyte layer, and negative electrode layer are interposed between the positive current collector and the negative current collector, or an electrolyte layer is interposed between the electrode layers for stacking. The method for manufacturing the all-solid-state battery comprises: when forming the electrode layer on the current collector, a preparation step of preparing a slurry consisting of at least an electrode active material and a solvent, and a preparation step of preparing a slurry consisting of at least electrolyte particles or electrolyte short fibers and a solvent; a stacking step of alternately coating at least the two types of slurries on the current collector in a thin film manner and stacking them in a manner of forming two or more layers, At least one of the electrode formation and the electrolyte layer formation is performed by coating using a spraying method, and the collector, electrode layer, or porous sheet serving as the coating target is heated, and the solvent is evaporated by more than 95% within 5 seconds after the sprayed particles adhere to the target to form the electrode or electrolyte layer.

2. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: The number of layers of each slurry is 2 to 15.

3. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: At least the positive electrode slurry among the slurries contains a conductive auxiliary agent.

4. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: The conductive agent is prepared as a separate slurry, and the conductive agent particles or fibers are dispersed in such a manner that at least the conductive agent particles or fibers do not form a film, and the active material particles are coated on the selected electrolyte particles or fibers.

5. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: At least the electrode slurry and the electrolyte slurry contain an inorganic or organic binder.

6. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: The electrolyte layer is formed by applying the electrolyte layer slurry in a thin film form on the positive electrode layer or the negative electrode layer formed on the electrode, or on the porous sheet for electrolyte.

7. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: The spraying is performed in a pulse mode of 1 to 1000 Hz, the distance between the target object and the nozzle is 5 to 60 mm, and the slurry spray particles are sprayed toward the target object with impact force, the solvent and non-volatile components of the slurry are separated instantly, and the solvent evaporates.

8. The method for manufacturing an all-solid-state battery according to claim 1, characterized in that: The electrolyte is a sulfide, and exhaust means is connected to the downstream of the pipeline of the electrode layer formation and electrolyte layer formation process, and dehumidification means is provided upstream.

9. The method for manufacturing an all-solid-state battery according to any one of claims 1 to 8, characterized in that: The method comprises: a process of forming a negative electrode on a negative electrode collector, a process of forming a positive electrode on a positive electrode collector, a process of forming an electrolyte layer on the negative electrode or the positive electrode, or a process of forming an electrolyte layer with a porous substrate as a skeleton and inserting an electrolyte layer between the positive and negative electrode layers.

10. The method for manufacturing an all-solid-state battery according to claim 9, characterized in that: The all-solid-state battery is manufactured by a roll-to-roll method.

Citation Information

Patent Citations

  • Liquid coating method

    JP1994086956A

  • Method for spraying liquid or heating melt

    JP1996309269A

  • Method for manufacturing all-solid battery

    JP2014212022A

  • Electrode, manufacturing method thereof and all-solid lithium ion battery

    JP2017174805A